Comparative Study of Vitamins Nutrient from Marsilea quadrifolia Linn. - Jadhao, K.D.; Wadekar, M.P. (Asian Journal of Chemistry, 2010)
The present study deals with the study of availability of vitamin nutrients form M. quadrifolia Linn. Fresh as well as shade dried material was used for estimation of vitamin B1 (thiamine), vitamin B2 (riboflavin) and vitamin C (ascorbic acid).